The historical villages of Mendoza river border head area: A testimony of finisecular modernity (1890-1950) - Bianchi Palomares, Pablo Federico Ricardo (Universidad ORT Uruguay, 2020)
The mountain towns that mark the high valley of the Mendoza River, in the homonymous province of central west Argentina, are testimony of the Turn of the century modernity, since its appearance in the context of the implantation of the Trasandino Railway, at the end of the 19th century. Their presence in the mountain itinerary was fundamental since they facilitated trade and transport, in the westernmost section of the route that linked Buenos Aires with the cities of Santiago and Valparaíso in the neighboring country of Chile. Being located in close relationship with the Mendoza River, and in a geographical support of unique characteristics; they acted as structuring of the territory, with a systemic disposition that defined the border territory until the middle of the 20th century.The problem that motivates this work is based on the detection of a vacancy referring to the comprehensive reading of cultural assets, linked to the upper section of the Mendoza River. The contributions which were made recently are fragmentary, especially in relation to the assets that consolidated the territory of the Mendoza high mountain area; at Tourism-, Road- and Service- Levels. With the help of the descriptive-explanatory analysis of four historical towns, the study seeks to fill an inclusive approximation and to help understanding the fundamental role they played in the process of gradual occupation of the high mountain territory, which began in the modernity.